A Case Study on Rising Petrol and Diesel Prices in Fourteen Cities of India (Journal of Pharmaceutical Negative Results, 2022)
The purpose of this study is to use the regression and correlation methods to analyze rising petrol and diesel prices in various Indian cities. A substance that is burned and transformed into energy is referred to as fuel. Coal, petrol, diesel, or any other material that reacts with another material to produce energy that may be used for work can be referred to as fuel. The purpose of this research is to examine the pricing of gasoline and diesel in fourteen cities across India. The statistical methods used to interpret the data are correlation, regression and ANOVA. There are also graphical representations, tabular columns, and scatter diagrams.